City Library Management Based School (A Site Study at Mobile Library of Magelang City) - Sunardiyana, Sunardiyana (2011)
The objectives of this research are (1) to describe the characteristic of borrowing and returning service of library books at around mobile library, and (2) to describe the characteristic of reference services of library books at around mobile library. This is a qualitative research conducted in of library books at the around mobile library at Magelang City using an technographic approach. The main subject of this research is the library manager, librarian and student of existing town of Magelang. Data collection techniques used in this research is observation, interview and documentation. Data analysis in this research using data analysis techniques is that arranged in a site. The validity of the data in this research includes credibility, transferability, dependability, and conformability. The results of this research show that (1) in system of library services, there are two service systems that are open systems (open access) and a closed system (close access) that still done annually. Service borrowing and returning books are done on scheduled that usually done in spare time or in accordance time from school's requests. In library lending service at around mobile library Magelang City, the students must have a library card. Students are only allowed to borrow as much as 2 books with a length of borrowing time for one week. And for students who are late returning the book, they will get fine in accordance with existing rules. (2) To attract students to come to library, the manager tried to increase the number of library reference that they owned. However, due to limited space so it can not be fulfilled. Number of books in around mobile library approximately to 2000's that consists of general book, philosophy and psychology, religion, social sciences, languages, pure sciences, applied sciences (technology), arts and entertainment sports, literature, geography and general history, fiction, magazines and newspapers. References in the library are arranged according to the type of book. This was to facilitate the search references that they need, the management has prepared a manual catalog.